Tandem dances choreographing immersive performance - Ritter, Julia M. (Oxford studies in dance theory, 2020)
'Tandem Dances' proposes dance and choreography as frames through which to examine immersive theatre, more broadly known as immersive performance. Indicative of a larger renaissance in storytelling during the digital age, immersive performance is influenced by emerging computer technologies, such as virtual reality and advances in video-gaming, as well as increased interest in new forms of experiential entertainment. The idea of tandemness - suggesting motion that is achieved by two bodies working together and acting in conjunction with one another - is critical throughout.